(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Background: The iron deficiency anemia along with hyperphosphatemia are the main complications of dialysis patients. Traditional ironsupplement has been failed to correct iron deficiency anemia, therefore, the current study aimed to investigate the efficacy and tolerability ofnew phosphate binder, ferric citrate, in a sample of Iraqi patients with end stage renal disease on maintenance hemodialysis.Method: Prospective, randomized, open label, active controlled trial was conducted in one center for dialysis in Babylon governance.Patients were randomized to receive ferric citrate with dose of 6 g/d and calcium carbonate with dose of 3 g/d for eight weeks. Hemoglobinconcentration, mean corpuscular hemoglobin concentration and count of RBCs along with iron store parameters were measured. The adherenceand gastrointestinal side effects were reported at the end of study.Results: A total of 50 patients were completed the study. Ferric citrate group showed elevation in count of RBCs, hemoglobin concentration,MCH-C and reduction in use of IV iron and erythropoietin as well as increased iron store which evidenced by elevation of ferritin level in theparticipants. There were similar adverse effects in both groups, with good adherence seen in ferric citrate group.Conclusion: A treatment with ferric citrate for 8 weeks was observed to effectively improve anemia in a sample of Iraqi patients with endstage renal disease on maintenance hemodialysis. In addition, the use of intravenous iron and erythropoietin was reduced in ferric citrate groupwith well tolerability throughout the study period. Ferric citrate may be useful alternative for restoring iron level in hemodialysis patients.